1980
DOI: 10.1016/0039-6028(80)90118-1
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption and incorporation of oxygen on Cu(100) and its reaction with carbon monoxide; comparison with Cu(111) and Cu(110)

Abstract: Ellipsometry, LEED, Auger electron spectroscopy and monitoring of work function changes have been used to study the interactions of 02 and N20 with a clean annealed Cu(100) surface and of the reaction of CO with sorbed oxygen. Gas pressures were in the range IO-'--lo4 Torr and crystal temperatures varied between 25-4OO'C. The initial interaction of oxygen with Cu(100) occurs in three stages. Oxygen chemisorbs with an initial sticking coefficient of -10T2 at room temperature and an apparent activation energy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 107 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…We can thus conclude that the hydrogen-oxygen reaction on Cu surfaces is determined by the initial formation of adsorbed OH groups (with activation energies in the range 80-92 kJ/mol) and that the reaction is not particularly plane-specific. Similar conclusions have been drawn with respect to the CO oxidation on the low index copper faces [4]. The activation energy for the Langmuir-Hinshelwood reaction of adsorbed CO and 0 is 75-84 kJ/mol, independent of the crystallographic orientation.…”
Section: Discussionsupporting
confidence: 66%
“…We can thus conclude that the hydrogen-oxygen reaction on Cu surfaces is determined by the initial formation of adsorbed OH groups (with activation energies in the range 80-92 kJ/mol) and that the reaction is not particularly plane-specific. Similar conclusions have been drawn with respect to the CO oxidation on the low index copper faces [4]. The activation energy for the Langmuir-Hinshelwood reaction of adsorbed CO and 0 is 75-84 kJ/mol, independent of the crystallographic orientation.…”
Section: Discussionsupporting
confidence: 66%
“…With the combination ellipsometry-AES-LEED, Habraken et al have observed linear relations between the change in the ellipsometric parameter A at h = 632.8 nm and the oxygen coverage 6 in the chemisorption stage on Cu( 111) [ 11, Cu( 100) [2] and Cu(ll0) [3,4] (0 5 0.5 oxygen atoms per surface metal atom). After this stage a further uptake takes place, accompanied by reconstruction of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The observed constant coverage in the range of 45-3 X l0~L may be ascribed to a nucleation process prior to the formation of the c(6 X 2) structure as has been observed for Cu (100) [15]. As the equilibrium oxygen pressure for bulk oxide formation at room temperature is less than 10'~Torr [16], the observed constant coverage can not be due to an equilibrium process.…”
Section: Sorption Of Oxygen On Cu(11o)mentioning
confidence: 64%